Integration of Islamic Values in Learning Indonesian Language at Madrasah Ibtidaiyah - Islamiati Putri, Amalia; Siti, Fatonah (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2023)
The purpose of this study was to describe how the integration of Islamic religious values ​​in learning Indonesian MI Muhammadiyah Lessons Plus. The subjects of this study were Indonesian teachers of class III MI Muhammadiyah Plus Lessons. The topic of this research is Islamic values ​​in Indonesian education at MI Muhammadiyah Plus Lessons. This research is a field research using qualitative methods. Materials were obtained from MI research and also from literary sources related to the subjects studied. The approach used is descriptive qualitative with data collection techniques, observation and interviews to analyze data with inductive qualitative descriptive inference. The results of this study indicate that Indonesian language teachers in class MI Muhammadiyah Plus Lesson III integrate the existing characters in learning Indonesian, namely with different teaching methods depending on the material being taught. Islamic values ​​are integrated in every school subject, especially in the Indonesian language class, it is hoped that students will be able to apply these Islamic values ​​in everyday life.